Return-to-learn after concussion in Washington state public high schools during the COVID-19 pandemic - Shyam J Deshpande; Aspen Avery; Julian Takagi-Stewart; Brianna Mills; Qian Qiu; Monica S Vavilala (Concussion)
Aim: To understand academic support structures for Washington state public high school students with concussion during the COVID-19 pandemic. Materials & methods: Prospective, repeated cross-sectio...